THE ANALYSIS OF UTENA DISTRICT RESIDENTS’ OPINION OF UTENA LOCAL LORE MUSEUM ACTIVITY - Narkūnienė, Ramutė; Striupienė, Simona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
In the article, the authors analyze the Utena district residents’ opinion of Utena Local Lore Museum activity. The purpose of the research is to analyze the Utena district residents’ opinion of Utena Local Lore museum activities and to present proposals for improving Utena Local Lore Museum activity. During the research, a questionnaire survey was conducted. Data collection methods - analysis of scientific literature and sources, quantitative research (questionnaire survey). The article analyzes Utena district residents’ opinion of Utena Local Lore Museum activity from a theoretical point of view and presents the results of the conducted research. It is concluded that according to the results of the conducted research, visiting the Utena Local Lore Museum is encouraged by various entertainments, exhibitions, events and education, but, according to the respondents, all this should be related to the Utena region and its history. Repeated visits of the respondents to the museum would be determined by updated expositions, offered entertainment, and interesting presentations